REMOTE SENSING OF THE STATE OF THE VEGETATION COVER OF THE TERRITORY OF THE BULGARIAN BLACK SEA: REMOTE SENSING OF THE STATE OF THE VEGETATION COVER OF THE TERRITORY OF THE BULGARIAN BLACK SEA - Zdravcheva, Neli (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This paper is devoted to the multispectral processing of satellite images in order to establish the actual state of the vegetation cover. As a result of conducted experiments, the vegetation on the territory of the Bulgarian Black Sea coast was studied. For this purpose, new indexed images have been generated from appropriately selected multispectral images, which visually reveal the actual state of the vegetation cover and provide objective and timely data. They could serve to manage and other decisions (in the field of ecology, forestry, agriculture, etc.), for environmental assessments and expertise, for scientific research and other projects.